Epitranscriptomic modifications for enhancing abiotic stress resistance in plants - Zeng, Yunmin; Muhammad, Abid; Wan, Lingyun; Gao, Chenlu; Zhao, Pinyao; El-Sappah, Ahmed H. (Frontiers in Plant Science, 2025)
Climate change significantly impedes agricultural growth, development, and production. Plants adapt to environmental changes via the plasticity given by essential genes, which are regulated at the post-/transcriptional level. Gene regulation in plants is a complex process governed by various cellular entities, including transcription factors, epigenetic regulators, and non-coding RNAs. Successful studies have confirmed the function of epigenetic alterations such as DNA methylation/histone modification) in gene expression. In recent years, a highly specialized science known as “Epitranscriptomics” has emerged. Epitranscriptomics studies post-transcriptional RNA chemical alterations seen in all living organisms that alter RNA’s structural, functional, and biological properties. Our minireview interpreted about understanding the molecular pathways: RNA changes and stress-responsive gene regulation. Additionally, the interplay between epitranscriptomics and other regulatory levels has been addressed. In addition, we reviewed technical breakthroughs in epitranscriptomic research, including tools and techniques.